Strategi Pemasaran Dalam Upaya Meningkatkan Penjualan Jasa dan Brand Awareness Pada Perusahaan Jasa Pelaksana PT. National Utility Helicopters - Ajeng Niken Ivana Putri (PT FORMOSA CENDEKIA GLOBAL, 2022)
PT. National Utility Helicopters is a company engaged in the aviation industry with a focus on helicopter rental units. The purpose of this research is to find out the marketing mix strategy used by PT. National Utility Helicopters as well as knowing the Strengths, Weaknesses, Opportunities and Threats contained in the Company. PT. National Utility Helicopters. This study uses a qualitative type of research. Based on the results of research that has been obtained by marketing strategies carried out by PT. National Utility Helicopters is good enough. The results of the SWOT analysis obtained from this study found 4 strengths and 4 Weaknesses owned by PT. National Utility Helicopters and 3 Opportunities and 2 Threats owned by PT. National Utility Helicopters.